EXPLORING TRAVEL SELFIES: THE CASE OF BARCELONA - Raquel Camprubí; Pamela Rojas (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2021)
This paper aims to explore the relationship between characteristics of selfie-takers and the destination image depicted in the background of the photographs. Through a content analysis based on a sample of 1,537 selfies taken in Barcelona’s most visited places and shared on Instagram, the authors were able to identify the most relevant elements and tourist scenarios involved in these photographs, as well as the relationship that exists among certain features of the profile of selfie-takers. The study reveals that travel selfies are a viable tool, which contributes to destination image and is aligned with the image destination management organizations promote.